TiN Paper for Ultrafast-Charging Supercapacitors - Yao, Bin; Li, Mingyang; Zhang, Jing; Zhang, Lei; Song, Yu; Xiao, Wang; Cruz, Andrea; Tong, Yexiang; Li, Yat (Nano-Micro Letters, 2019)
Ultrafast-charging energy storage devices are attractive for powering personal electronics and electric vehicles. Most ultrafast-charging devices are made of carbonaceous materials such as chemically converted graphene and carbon nanotubes. Yet, their relatively low electrical conductivity may restrict their performance at ultrahigh charging rate. Here, we report the fabrication of a porous titanium nitride (TiN) paper as an alternative electrode material for ultrafast-charging devices. The TiN paper shows an excellent conductivity of 3.67 × 104 S m−1, which is considerably higher than most carbon-based electrodes. The paper-like structure also contains a combination of large pores between interconnected nanobelts and mesopores within the nanobelts. This unique electrode enables fast charging by simultaneously providing efficient ion diffusion and electron transport. The supercapacitors (SCs) made of TiN paper enable charging/discharging at an ultrahigh scan rate of 100 V s−1 in a wide voltage window of 1.5 V in Na2SO4 neutral electrolyte. It has an outstanding response time with a characteristic time constant of 4 ms. Significantly, the TiN paper-based SCs also show zero capacitance loss after 200,000 cycles, which is much better than the stability performance reported for other metal nitride SCs. Furthermore, the device shows great promise in scalability. The filtration method enables good control of the thickness and mass loading of TiN electrodes and devices. Highlights 1 The superior conductivity and unique porous electrode structure in the TiN paper enable fast charging by simultaneously providing efficient ion diffusion and electron transport. 2 The TiN paper-based supercapacitors exhibit charging/discharging at an ultrahigh scan rate of 100 V s−1 in a wide voltage window of 1.5 V in Na2SO4 neutral electrolyte and show zero capacitance loss after 200,000 cycles.